Sensibilidade in vitro e in vivo de isolados de Colletotrichum lindemuthianum (Sacc & Magn.) Briosi & Cav., a fungicidas sistêmicos - Gulart, Caroline Almeida (2009)
The sensitivity of ten isolated of Colletotrichum lindemuthianum the systemic fungicides was evaluated in vitro and in vivo, in experimental design was completely random with three replications. In the study in vitro, it was evaluated the percentage of germination of spores of the fungus when submitted to the benzimidazol fungicides: carbendazin and methyl tiophanate and the estrobilurins: azoxystrobin and pyraclostrobina. The methodology consisted in incorporate the fungicide to the agar at the final concentrations of 0; 0,1; 1,0; 10 and 100 ppm. With the germination data the DL50 (rate capable to inhibit 50% of the germination of spores) was calculated. For each fungicide was calculated the DL50, being observed differences in the sensitivity of isolated of C. lindemuthianum. Considering the fungicide carbendazin, race 65 presented low sensitivity while races 08, 81, 321 had been moderately sensible to this fungicide. In the case of the estrobilurins, all the isolated ones had revealed highly sensible to the fungicides azoxystrobin and pyraclostrobin, proving the effect of this chemical group on the germination of spores. In the in vivo evaluation, it was evaluated the DL50 having considered the injuries of C. lindemuthianum formed from the inoculation of a known concentration of spores in detached bean leaves submitted to the final concentrations of 0; 0,5; 1,0; 5,0; 10,0 and 50,0 ppm of tebuconazol and epoxiconazol. It was not observed difference among isolates, considering the classification of sensitivity proposed by Edgington al. (1971). However, it was verified great amplitude of values of DE50 between the isolated ones. Race 321 presented moderate sensitivity to the epoxiconazol, races 08 and 65 with relatively bigger values of DE50. The same occurred with race 81 with regard to epoxiconazol. The alteration in the sensitivity on C. lindemuthianum isolates, when submitted to the group of the benzimidazoles, was related to the frequency and pressure of selection imposed by repeated fungicides application. Regarding the triazoles, it was not observed differences in the classification of sensitivity between the isolates, showing that the use of these fungicides in the control of anthracnose did not produce a similar selective effect as observed with the fungicides tebuconazol and epoxyconazol.